Adhering to scientific and ethical criteria for scholarship of teaching and learning - Pool, Jessica; Reitsma, Gerda (Critical Studies in Teaching and Learning, 2023)
Despite expanding engagement in Scholarship of Teaching and Learning (SoTL), clear guidelines for ethical criteria for SoTL, and the implementation thereof remain limited. In this paper we critically reflect on how the ethics criteria and processes impact on lecturer engagement in SoTL, and we provide suggestions for lecturers, academic developers, and members of scientific and ethics committees on how to support research in teaching and learning, without losing the scholarliness of such research or hindering innovation in teaching. This paper provides a critical reflection on SoTL and ethics. Practical recommendations such as: the adaptation of ethical requirements, consultation between SoTL researchers and ethics committees and acknowledging that SoTL is not purely discipline-specific research, are provided. Taking these recommendations into account may support a better alignment between the ethical application process and the scientific approach of SoTL research.